2013
DOI: 10.1095/biolreprod.113.108266
|View full text |Cite
|
Sign up to set email alerts
|

Control of Spontaneous Activation of Rat Oocytes by Regulating Plasma Membrane Na+/Ca2+ Exchanger Activities

Abstract: Inhibiting oocyte spontaneous activation (SA) is essential for successful rat cloning by nuclear transfer (NT). This study tested the hypothesis that activities of the Na(+)/Ca(2+) exchanger (NCX) would decrease with oocyte aging and that SA of rat oocytes could be inhibited if the intraoocyte Ca(2+) rises were prevented by activating the NCX through increasing Na(+) concentrations in the culture medium. Elevating Na(+) levels in culture medium by supplementing NaCl inhibited SA of rat oocytes, while maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Interestingly, although exosome supplementation enhanced only ratio of ICM/TE to a similar level as that in nonrenewal group (Table 3), no overt difference in pregnancy or calving rate was detected between these two groups, suggesting ratio of ICM/TE during cell lineage specification might be a more critical marker than others for the following in vivo development to term. This suggestion actually also supports previous findings that satisfactory blastocyst rate of SCNT embryos did not guarantee the following in vivo development to term [49, 52]. …”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, although exosome supplementation enhanced only ratio of ICM/TE to a similar level as that in nonrenewal group (Table 3), no overt difference in pregnancy or calving rate was detected between these two groups, suggesting ratio of ICM/TE during cell lineage specification might be a more critical marker than others for the following in vivo development to term. This suggestion actually also supports previous findings that satisfactory blastocyst rate of SCNT embryos did not guarantee the following in vivo development to term [49, 52]. …”
Section: Discussionsupporting
confidence: 91%
“…Both the present study and our previous studies [31], [37] demonstrated that in the Sprague-Dawley rats, whereas many oocytes recovered 19 h post hCG injection underwent spontaneous activation during in vitro culture, spontaneous activation was less frequently observed in oocytes collected 13 h after hCG. To explore the mechanisms causing the difference in activation susceptibility between newly-ovulated and aged rat oocytes, the present results indicated that in the 13-h oocytes, an unknown activating stimulus (maybe the manipulation for their release from the oviduct) induced mild Ca 2+ rises, which activated NCX under a low ROS level (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…The Na + /Ca 2+ exchange has been observed in immature and mature mouse [34], [35], porcine [36] and rat [37] oocytes. However, although our recent study indicated a role for Na + /Ca 2+ exchange in the spontaneous activation of rat oocytes [37], systematic studies are lacking on roles of the Na + /Ca 2+ exchanger (NCX) activity in controlling postovulatory oocyte aging of different species. Furthermore, in previous studies the NCX activity was usually determined by functioning assays (by measuring Ca 2+ flux, for example), with little attention paid to the dynamic changes in NCX contents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, GO term analysis offered no striking outliers in functional categories within our screen results and suggests that preimplantation development equally requires all aspects of cellular and molecular function for success. Supporting this notion, previous studies have found essential roles during preimplantation for genes within each of these functional categories (including DNA/RNA/protein binding4546, catalytic activity4748, various transporter activity495051). …”
Section: Resultsmentioning
confidence: 70%